Exploring the therapeutic potential of edible Pleurotus mushroom species for oxidative stress and diabetes management - Karempudi Venkata Krishna; Jimmantiyur Madhappan Murugan; Haroon Khan; Munusamy Kumar; Veeramani Veeramanikandan; Ashraf Atef Hatamleh; Munirah Abdullah Al-Dosary; Karthikeyan Venkatachalam; Paulraj Balaji (Journal of King Saud University: Science, 2023)
Objectives: In this study, extracts from eight Pleurotus mushroom species were examined for their antioxidant properties. Methods: The pure cultures of eight Pleurotus were grown, harvested, air-dried, pulverized, and for various biological activities. Results: The methanolic extract of Pleurotus florida showed the highest concentrations of total phenolics, total tannins, and flavonoids. It also displayed the greatest antioxidant activity in the FRAP, ABTS, metal chelating, superoxide anion radicals, hydrogen peroxide, nitric oxide and DPPH assay. In the hydroxyl radical scavenging assay, Pleurotus florida and Pleurotus flabellatus showed notable effects in methanolic and acetone extracts, respectively. Moreover, Pleurotus florida demonstrated a strong antioxidant effect on β-carotene in methanolic extracts. The study also explored the potential of mushrooms as natural anti-diabetic treatments by targeting a key enzyme in biopharmaceuticals. Pleurotus florida's methanolic extract at a concentration of 1000 µg/ml exhibited significant α-amylase inhibition (99.02%), surpassing acarbose's efficiency at the same concentration (96.54%). Conclusion: Overall, the bioactive components from Pleurotus florida showed effective antioxidant and antidiabetic effects under in vitro conditions.